2014
DOI: 10.1111/bjd.12842
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and morphometric study of the androgenetic alopecic scalp using two- and three-dimensional analysis comparing regional differences

Abstract: The morphology of the AGA scalp has been characterized. The terminal-to-vellus hair ratio in the occipital (normal) region was different from that in the frontal (alopecic) region. Moreover, sebaceous glands were larger in the frontal alopecic region than in the occipital region. These larger glands may be associated with other dermatological pathologies, such as seborrhoeic dermatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Androgenetic alopecia (AGA) is the most frequent form of alopecia characterized by progressive patterned hair loss, stepwise miniaturization of hair follicles, and change in hair cycle 1 caused by androgens and genetic factors 2 . Previous studies have indicated that scalp anatomy changes significantly with aging or alopecia 3‐7 …”
Section: Introductionmentioning
confidence: 99%
“…Androgenetic alopecia (AGA) is the most frequent form of alopecia characterized by progressive patterned hair loss, stepwise miniaturization of hair follicles, and change in hair cycle 1 caused by androgens and genetic factors 2 . Previous studies have indicated that scalp anatomy changes significantly with aging or alopecia 3‐7 …”
Section: Introductionmentioning
confidence: 99%
“…Cross talk occurs between androgens and the Wnt-betacatenin signaling pathway that leads to hair loss. At the somatic stem cell level, androgens promote differentiation of facial hair dermal papillae but inhibit it at the scalp [1]. There are different stages in which hair loss takes place in the scalp as classified by Norwood.…”
Section: Androgenic Alopeciamentioning
confidence: 99%
“…Prior to the usage, the skin was carefully examined to ensure absence of holes or crevices. Later, the skin was mounted on a receptor compartment of the Franz diffusion cell with the subcutaneous region facing towards the donor compartment [20,21]. The receptor compartment was filled with 15 ml of pH 7.4 PBS, maintained at 37 ± 1 C. One ml of FES was applied to the epidermal surface of the frontal scalp skin of human cadaver and covered with paraffin film.…”
Section: In Vitro Permeation Across Scalp Skin Of a Human Cadavermentioning
confidence: 99%